Heavy users of e-banking and Customer Experience Management: evidences on intrinsic motivation. (10th March 2010) - Cruz, Pedro; Salo, Jari; Munoz-Gallego, Pablo; Laukkanen, Tommi
The study provides insights into experiential marketing in a predominantly goal-directed service like internet banking. A model is proposed that combines two complementary approaches in the analysis of experience: a cognitive approach based on quality and an affective approach based on emotions. 754 valid observations have been collected through an online survey among heavy users of internet banking. Latent scores were used to compare consumers' perceptions, differences in demographics and usage variables. The results show that both perceived quality and flow state are major determinants of satisfaction and positive emotions. The paper contributes to electronic business by examining the relationships between consumer motivation, service quality, satisfaction, flow experiences and behavioural variables.